A venda pessoal de seguros de automóveis: principais competências profissionais dos corretores de seguros - CARNEIRO, Carlos George Aguiar (2016)
Brazilian insurance market has shown great vitality. It continues to grown, even in years of economic recession. Along the last ten years, its income has increased, reaching the high percentage of 252,5%, while PIB – Gross Domestic Production – has only 45,13%. In the year 2015, these incomes represented almost 4% of PIB. The insurance-broker indeed an important factor of this growing, building the real, great selling-branch of insurance companies. This important profession had recognized by law, since 1964. This selling-professional has more and more been required for his/her high importance on a very highly competitive market. Since then, the insurance-broker began being required on the field of insurance for autos, for high level of importance on the insurance-market. Researching, on this area, is strictly related to the real capacity of the broker for personal selling of car-insurance. The main goal on this field of special activities is the definition of competence or ability of the broker, it can gather new knowledge and values, seeking, at the same time, for renovation and increasing the insurance market, contributing for bettering performance on brokerage, as the whole. The methodological way it chose was the explorative/qualitative one, with the utilization of simple statistical tools. It chose and adapted Delphi-Method, through the creation of a panel, with the help of experts/specialists. The final results of this research generated a list of 12 competences, divided into technical and behavior ones.